1988
DOI: 10.1055/s-2007-1018117
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sphincterotomy: Long-term Results in 408 Patients with Complete Follow-up

Abstract: Endoscopic sphincterotomy was performed in 469 patients for the treatment of biliary calculi, with procedure-related morbidity of 6.3% and mortality of 0.4%. Long-term follow-up to 10.5 years (mean 3.7 years) was completed in all of 408 patients at least six months postsphincterotomy. Recurrent stones developed in 21 patients (5.8%) after a mean of 2.4 years (range 4 months to 7 years); in 6 after 3 years. Eight patients reformed stones more than twice at a mean interval of 1.8 years (range, 5 months to 3.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 0 publications
2
50
1
Order By: Relevance
“…Its success rate exceeds 90%, and it has been accepted as the best nonsurgical treatment for common bile duct stones [29][30][31][32][33] . However, EST is still associated with an 8%-12% rate of acute complications, such as bleeding, perforation, cholangitis, and post-procedure pancreatitis [11,25,[34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…Its success rate exceeds 90%, and it has been accepted as the best nonsurgical treatment for common bile duct stones [29][30][31][32][33] . However, EST is still associated with an 8%-12% rate of acute complications, such as bleeding, perforation, cholangitis, and post-procedure pancreatitis [11,25,[34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…In negative history of biliary reconstruction, transpapillary endoscopic treatment is indicated for patients without bile duct strictures. However, no studies with a large number of participants were conducted to assess transpapillary endoscopic treatment of hepatolithiasis without choledocholithiasis, and most reports described concurrent choledocholithiasis [212][213][214]. Tanaka et al [212] conducted EST in 57 patients with concurrent hepatolithiasis and choledocholithiasis and reported that the stones were completely removed in 24 patients (42.1%), including three patients with spontaneous stone passage.…”
Section: Commentarymentioning
confidence: 99%
“…It has therefore had a widespread acceptance for decades (1,2). On the one hand, it is possible that advancing technology and overall improved quality of medical care allow for better outcomes, but on the other hand, more aggressive approaches in the elderly and in those patients with higher numbers of medical coexisting conditions might confer a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%